A Discourse on Nepal Army’s Role in Conservation - Rai, Anu (Unity Journal, 2022)
Nepal prides itself as a conservation success story. Credit goes to the Nepal Army for their involvement in multiple conservation activities. They are at the forefront of conservation work in Nepal being stationed in the protected areas and involved in tracking down wildlife trade, controlling encroachment and deforestation, supporting rehabilitation of wild species, and much more. The results are visible having achieved zero poaching years of rhinos and other endangered species. The Nepal Army has thereby provided a great conservation service. But there is a lack of review on how their involvement has been perceived. T , and Part III presents views on rethinking the engagement. For this, google scholar was examined to obtain relevant papers using a combination of search keywords – “Nepal Army”, “Nepal military”, “conservation Nepal”, “civil-military relations Nepal” or its derivatives. Additional papers and newspaper articles pertaining to conservation discourse were also reviewed. Informal interviews with the Sonaha communities near the community forest of Bardiya National Park was also conducted. The review suggests that there is a need to rethink Nepal Army’s involvement in conservation for promoting inclusive conservation and maintaining amicable civil-military relationships.